Competence, Work Life Balance, Work Ethic and Performance of Cooperative Employees in Abiansemal District - Putra, I Dewa Made Arik Permana; Putra, I Gede Cahyadi; Yuliastuti, Ida Ayu Nyoman (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
Employee performance is the result output obtained from completing one's work or responsibilities to achieve company goals. There is a decline in the performance of Cooperative employees in Abiansemal District which can be seen from the failure to achieve loan realization targets. This is due to the low level of competence possessed by employees work life balance employees and the low work ethic of employees. This shows that employee performance is influenced by several factors, namely competence, work life balance and work ethic. The population in this study was the Head of Cooperatives in Abiansemal District, totaling 114 people. The data collection methods used were observation, interviews, questionnaires and documentation. The data analysis technique used is multiple regression analysis. The test results show that competency, work life balance and work ethic has a positive and significant effect on employee performance at the Cooperative in Abiansemal District.